Prevalence of parodontopathogenic microflora in patients with valvular pathology of the cardiovascular system - Mazur, I.; Vitovsky, R.; Slobodyanyk, M. (Actual Dentistry, 2018)
Summary. The relationship between pathological processes in various organs and systems of the organism remains one of the most complex. Most scientists recognize the pathogenetic relationship between inflammatory diseases of periodontal tissues and general somatic pathology. The aim of the study was to investigate the prevalence of parodontopathogenic microflora in patients with acquired heart defects based on clinical and microbiological studies. Material and methods. The study involved 30 middle-aged patients with generalized periodontitis and valvular heart disease. All patients were given general-clinical, dental, periodontal examination of the oral cavity. The microbiological study using the PCR method was performed on the removed heart valves and in the periodontal pockets of patients with acquired heart defects. Results of the study showed that all patients (100 %) undergoing surgical treatment on the heart valves revealed generalized periodontitis of varying degrees of severity. Total bacterial insemination (TBI), namely staphylococcal and streptococcal microflora, was detected in all patients (100 %), both in periodontal pockets and on valvular heart. Significantly, the prevalence of periodontal pocketing (TBI = 5.55 Lg (5.00–5.78)) (p < 0.001), compared with heart valves (LSD = 3.7 Lg (3.3– 3.9)) was higher. There was a lack of a correlation relationship (r = 0.118; p = 0.533) between the degree of indigestion of periodontal pockets and heart valves. The results of microbiological studies have shown a high prevalence of parasitogenous heart disease in the parodontopathogenic microflora of the heart valves. A high prevalence among parodontopathogens was detected in Porphyromonas gingivalis (60 %). Less prevalence was detected in T. denticola (40.0 %); T. forsythia (36.7 %); P. intermedia (10.0 %) and Aggregatibacter actinomycetemcomitan (10 %). The highest prevalence among periodontal pathogens in periodontal pockets was also found in P. gingivalis (86.7 %). Conclusions. Significant prevalence of periodontal diseases (100 %) among patients with acquired heart defects leads to high levels of microbial contamination with staphylococcal and streptococcal microorganisms of periodontal pockets and, as a consequence of transient bacteremia, intractable heart valves. Detection of parodontopathogenic microflora on the aortic and mitral valve of the heart may adversely affect the course of heart disease, deepen heart failure. Key words: chronic periodontitis, valvular heart disease, mitral valve stenosis, aortic stenosis, real-time polymerase chain reaction (RT-PCR)